An investigation into geometric ratios of the sunken courtyards in traditional Iranian houses (a field study on Yazd and Kashan) - Naseri, Hosein; Amini Farsani, Zahra (Journal of Architecture and Urbanism, 2022)
In Iranian architecture, the emphasis on the use of geometric ratios such as human scale and modularization, caused beauty and harmony. Unfortunately, in contemporary architecture, the use of these scales has been forgotten, and their presence has been diminished. Therefore, the main goal of the present study was to analyze and evaluate the geometry and proportions used in six remaining traditional Iranian sunken courtyards in Yazd and Kashan. For each house, the length, width, height and the ratio between these dimensions were measured for the sunken courtyard, courtyard and earth of the case studies. Then, to find out which kind of proportions were used in these sunken courtyards, we proposed some statistical tests to compare our measurements with the traditional proportions used. In the end, the results showed that the proportions used in the design of the sunken courtyard, courtyard, and earth of the case studies are related and the traditional Iranian sunken courtyards have been designed mostly based on the use of Gereh (a unit of measurement), which was the most appropriate and most widely used scale in housing architecture.